Impact of treatment of hyperkalaemia on quality of life: design of a prospective observational cohort study of long-term management of hyperkalaemia in patients with chronic kidney disease or chronic heart failure in Japan - Ken-ei Sada; Shunichi Fukuhara; Hajime Yamazaki; Yosuke Yamamoto; Jui Wang; Yugo Shibagaki; Yoshihiro Onishi; Takafumi Wakita; John E Ware; Toshitaka Yajima (BMJ Open)
Introduction Hyperkalaemia (HK) is a frequent complication in patients with chronic kidney disease (CKD) and/or chronic heart failure (CHF). HK must be managed, both to protect patients from its direct clinical adverse outcomes and to enable treatment with disease-modifying therapies including renin–angiotensin–aldosterone system inhibitors. However, the experiences of patients undergoing treatment of HK are not clearly understood. Optimising treatment decisions and improving long-term patient management requires a better understanding of patients’ quality of life (QOL). Thus, the aims of this research are: (1) to describe treatment patterns and the impact of treatment on a patient’s QOL, (2) to study the relationships between treatment patterns and the impact of treatment on a patient’s QOL and (3) to study the relationships between the control of serum potassium (S-K) and the impact of treatment on a patient’s QOL, in patients with HK.Methods and analysis This is a prospective cohort study with 6 months of follow-up in 30–40 outpatient nephrology and cardiology clinics in Japan. The participants will be 350 patients with CKD or CHF who received their first potassium binders (PB) prescription to treat HK within the previous 6 months. Medical records will be used to obtain information on S-K, on treatment of HK with PBs and with diet, and on the patients’ characteristics. To assess the impact of treatment on a patient’s QOL, questionnaires will be used to obtain generic health-related QOL, CKD-specific and CHF-specific QOL, and PB-specific QOL. Multivariable regression models will be used to quantify how treatment patterns and S-K control are related to the impact of treatment on a patient’s QOL.Ethics and dissemination Institutional review boards at all participating facilities review the study protocol. Patient consent will be obtained. The results will be published in international journals.Trial registration number NCT05297409.